TECHNOLOGY SCIENCE TRAINING INTEGRATION - Ibragimova Maryamkhan; Mirzakhmedova Khojirakhan (International Journal of Artificial Intelligence for Digital Marketing, 2024)
To improve students' learning experience and increase their ability to solve complex problems, this service aims to integrate technology training with science. Service methods include teacher training in the use of technology in science teaching, creating an integrated curriculum, interdisciplinary workshops and seminars, and collaborative projects between students from various scientific disciplines. Expected outcomes include increasing students' understanding of the relationship between science and technology, developing integrated learning materials, and increasing students' ability to apply technology in a science context. One of the results of this service is improving the quality of education through the use of a comprehensive learning approach, developing students' skills in line with the demands of the future job market, and increasing students' interest in science and technology through interesting learning experiences